VIRTUAL REALITY THERAPY: MOTOR COORDINATION AND BALANCE ANALYSIS IN CHILDREN AND TEENAGERS WITH DOWN SYNDROME - Gouveia Reis, Juliana Ribeiro; Neiva, Cassiano Merussi [UNESP]; Pessoa Filho, Dalton Muller [UNESP]; Ciolac, Emmanuel Gomes [UNESP]; Lopes Verardi, Carlos Eduardo [UNESP]; Cruz Siqueira, Leadro Oliveira da [UNESP]; Goncalves, Danielle de Freitas; Silva, Giuliano Roberto da; Hiraga, Cynthia Yukiko [UNESP]; Marques Tonello, Maria Georgina (Univ Extremadura, Fac Ciencias Deporte, 2017)
Introduction: The aim of the study was to evaluate the effects of Virtual Reality Therapy on motor coordination and balance of children and adolescents with Down Syndrome. Material and Methods: It is an analytical, prospective and quantitative study. This study included 12 participants were divided into two groups, five of them were part of the Control Group which performed regular institution activities, and the Protocol Group was composed of seven individuals who participated in the Virtual Reality Therapy program and also performed regular institution activities. First, the participants underwent an anthropometric assessment, Korperkoordinatonstest Fur Kinder and Pediatric Balance Scale. The Virtual Reality Therapy program consisted of 16 sessions of 20 minutes each. After the program the participants were reassessed. Results and Discussion: There was a statistically significant increase, in motor coordination of Protocol Group. The balance increase was also statistically significant in the final score obtained in Protocol Group, being 46.86 + 7.98 to 53.57 + 1.99. A negative correlation was recorded between body mass index and the value obtained in the Pediatric Balance Scale test, with r = -0.76 and p = 0.04. The Control Group showed no significant changes in any of the variables. Discussion: We conclude that performing the Virtual Reality Therapy program, conducted in short sessions on average 12 minutes, associated with normal activities of the institution, may be included as an adjunct to children and adolescents with Down Sindrome physiotherapy treatment, contributing to a better performance in motor coordination and balance
Keywords: physical rehabilitation; down syndrome; virtual reality